Searching for outbursts in the ground-based photometry of 67P/Churyumov–Gerasimenko. Issue 3 (19th October 2022) - Gardener, Daniel; Snodgrass, Colin; Ligier, Nicolas
ABSTRACT: 67P/Churyumov–Gerasimenko is a Jupiter-family comet that was the target of the Rosetta mission, the first mission to successfully orbit and land a probe on a comet. This mission was accompanied by a large ground-based observing campaign. We have developed a pipeline to calibrate and measure photometry of comet 67P during its 2016 perihelion passage, making use of all visible wavelength broad-band imaging collected across a wide range of facilities. The pipeline calibrates the brightness of the comet to a common photometric system (Pan-STARRS 1) using background stars within the field allowing for compilation and comparison of multiple data sets. Results follow the predictions based on previous apparitions: 67P shows no obvious change in activity levels from orbit-to-orbit and coma colours remain constant throughout the apparition. We detected an outburst on 2015 August 22 of ∼0.14 mag. The brightness and estimated mass of this outburst puts it in line with the outbursts directly observed on the nucleus by Rosetta. An in situ outburst was observed at the same time as the one seen from the ground; however, linking these two events directly remains challenging.